Methane production and energy partition in sheep fed timothy silage- or hay-based diets - Santoso, B; Mwenya, B; Sar, C; Takahashi, J (Indonesian Journal of Animal and Veterinary Sciences, 2007)
Methane is produced as a result of anaerobic fermentation of the soluble and structural carbohydrates by methanogens in the rumen of ruminant animals. Removal of methane from rumen represents a loss of approximately 7.22% of gross energy intake.Â  Four ruminally fistulated Cheviot wethers were used in a crossover design to determine methane production and energy partition in sheep fed timothy silage- or hay-based diets. The experimental diets consisted of either timothy silage or timothy hay and a commercial concentrate (85:15, on DM basis). Variables measured were nutrients digestibility, energy balance and methane production. Apparent digestibilities of DM, OM, CP, NDF, ADF, cellulose and hemicellulose were significantly higher (P<0.05) on sheep fed silage-based diet than those fed hay-based diet. Sheep fed silage-based diet had greater (P<0.01) urinary energy loss, methane and heat production, but lower (P<0.05) fecal energy loss. Methane production, either expressed as g kg-1 dry matter intake or g day-1 was markedly lower (P<0.05) in hay-based diet as compared to silage-based diet. There was a strong relationship between methane production (g day-1) and NDF digested (g day-1) (R2 = 88.4%, P<0.001). Methane production expressed as g kg-1 NDF digested in silage-based diet was higher (P<0.05) than in hay-based diet (66.44 vs 62.70). These results indicate that methane release by sheep increased with increasing NDF digested. Key Words : Methane, Silage, Hay, Neutral detergent fiber, Sheep